FACEBOOK SEASON – A SURVEY OF CURRENT PRACTICES OF NATIONAL HUNTING ASSOCIATIONS FACEBOOK PAGES: THE CASE OF THE EU - Ponjiger, Igor; Matejević, Milosava; Stankov, Uglješa; Marković, Vladimir; Ristić, Zoran; Kovačević, Milutin; Barović, Vladimir (Turizam, 2021)
National hunters’ associations (NHAs) are non-governmental organizations (NGOs) dealing with topics of hunting and conservation. We believe that NHAs have an important role in promoting hunting, wildlife protection, and shaping a positive public opinion about these subjects. This paper explores the basic characteristics and activities of the official Facebook Pages of NHAs among EU countries. The results have shown that the official NHA Facebook Pages don’t use the potential visible through the number of registered hunters and Page followers. Also, certain parameters used in the paper show preferable Page content in order to achieve more engagement. The findings of this paper are the first step into understanding the use of Facebook in hunting promotion and will serve as a starting point for further research.
Keywords: hunting organizations; hunting tourism; social media